The micro-foundations of digitally transforming SMEs: How digital literacy and technology interact with managerial attributes - Zahoor, Nadia; Zopiatis, Anastasios; Adomako, Samuel; Lamprinakos, Grigorios (My University, 2023)
Research often illustrates the importance of digital transformation for small and medium-sized enterprises (SMEs), particularly during external disruptions. However, little attention has been devoted to how SMEs’ digital transformation occurs. Employing a micro-foundations perspective, this study investigates the effect of managers’ digital literacy (MDL) on SMEs’ digital transformation. We test a moderated mediation model using survey data from 158 SMEs operating in the United Arab Emirates. Our findings suggest that MDL impacts digital transformation through the usage of digital technologies. Moreover, the relationship between MDL and the usage of digital technologies is further moderated by managerial attributes (i.e., gender, education, and age). Theoretical and practical implications are discussed.
Keywords: Digital transformation; Digitial literacy; Emerging market; Managerial attributes; Micro-foundations; SMEs